Corvée in the Kingdom of Israel: Israelites, Canaanites', and Cultural Memory - Houston, Walter (Journal for the study of the Old Testament, 2018)
Archaeological evidence of certain cultural traits supports the witness of some biblical passages that the (northern) kingdom of Israel was ethnically diverse, with non-Israelite populations in the northern lowlands. Texts in Judges 1 and 1 Kings 9 stating that Canaanites', etc., were subjected to forced labour, the corvée, either by Israelite tribes or by Solomon, should be regarded as texts of cultural memory, justifying the actual practice of the kingdom of Israel in the ninth and eighth centuries BCE in restricting the corvée to non-Israelites. This article proposes that these texts should be placed alongside the story of the rebellion against the house of David in 1 Kings 12, which, although in its present form is written from the point of view of Judah, carries clear traces of its origin as cultural memory in Israel. Taken together, the texts suggest that the kingdom avoided imposing the corvée on ethnic Israelites.